AN ASSESSMENT OF DEPRESSION, ANXIETY AND STRESS AMONG COLLEGIATE ATHLETES - Mr. Sunil Kumar , Dr. Reeta Devi , Mr.Mahendra Singh Parmar , Mr Ashutosh Sharma , Mr. Malkhan Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this investigation university competitors, who used to participate in between school matches and competitions was chosen as subjects to survey the downturn, tension and stress. the specialist chose thirty (30) players of Lakshmibai public organization of physical training, Gwalior (M.P.). The age gathering of the subjects was run from (20-25) a long time. To quantify despondency, nervousness and worry among university competitors, a poll Depression Anxiety Stress Scale 42 (DASS 42) created by Lovibond and Lovibond (1995) was utilized to assess the downturn, tension and worry of the subjects. The information was gathered from the school players who used to partake in between school matches and competitions. the current examination, uncovers that Anxiety, gloom and stress were unprecedented among university competitors where sorrow has the least mean score (M= 7.60) with standard deviation (SD= 4.13) and nervousness has the most noteworthy mean score (M=9.13) with standard deviation (SD= 5.31) while mean score of pressure was (M=8.66) with standard deviation ( SD= 4.67). the examination additionally shows that the seriousness of gloom, and stress were ordinary in university competitors and the seriousness of tension was gentle in university competitors..